Russian foreign policy: what drives Russia's support for the al-Assad regime? - Levocz, Mary (AUC Knowledge Fountain, 2015)
The current crisis in Syria has left the international community divided on solutions regarding the ongoing civil war that has escalated far beyond protests calling for the removal of the al-Assad regime. The events unfolding in Syria have divided the international community into groups that staunchly oppose the al-Assad regime, such as the United States, the European Union, and other countries in the region, such as Qatar, Saudi Arabia, and Turkey, and those that oppose any pressure to the regime, such as Russia, China, and Iran. The primary purpose of this thesis is to determine why Russia would support such an unpopular, internationally isolated regime amidst the current instability in the Middle East. Secondly, this thesis will examine the internal factors that influence Russian foreign policy towards Syria, displaying that Russia’s support for the al-Assad regime goes far beyond Russian interests in Syria and Russian-Syrian relations. This research displays how Russia’s decision to back the Syrian regime has affected its international status in an attempt to demonstrate Russia’s largest foreign policy goal: great power status.